2023
DOI: 10.3168/jdsc.2022-0264
|View full text |Cite
|
Sign up to set email alerts
|

Influences of human contact following milk-feeding on nonnutritive oral behavior and rest of individual and pair-housed dairy calves during weaning

Abstract: Graphical Abstract Summary: This study evaluated the interactive effects of social housing and human contact following feeding, including scratching to mimic brushing, on nonnutritive oral behaviors and rest of dairy calves during weaning. Individually housed calves performed more pen-directed nonnutritive oral behavior than pair-housed calves, but provision of human contact reduced the duration of this behavior to a level that did not differ from pair-housed calves. Human co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Special management, such as providing environmental stimulation, may be needed for these calves under individual housing conditions (da Silva et al, 2022). For instance, additions to the environment of individually housed calves can reduce the occurrence of non-nutritive oral behaviors, such as providing hay (Downey et al, 2022), stationary brushes (Horvath et al, 2020) or human contact (Doyle and Miller-Cushon, 2022). Activity patterns of calves in the home pen as a personality trait are rarely explored for links with other behaviors and performance, but the current study has revealed its potential importance and how this measure can be easily collected with technology.…”
Section: Personality and Feeding Behaviorsmentioning
confidence: 99%
“…Special management, such as providing environmental stimulation, may be needed for these calves under individual housing conditions (da Silva et al, 2022). For instance, additions to the environment of individually housed calves can reduce the occurrence of non-nutritive oral behaviors, such as providing hay (Downey et al, 2022), stationary brushes (Horvath et al, 2020) or human contact (Doyle and Miller-Cushon, 2022). Activity patterns of calves in the home pen as a personality trait are rarely explored for links with other behaviors and performance, but the current study has revealed its potential importance and how this measure can be easily collected with technology.…”
Section: Personality and Feeding Behaviorsmentioning
confidence: 99%